Case Report on Sertoli Cell Tumor of Ovary (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
A 33 years old lady presented with history of irregular menstrual cycle followed by menorrhagia. USG revealed left ovarian solid mass but all tumor markers were within normal range. A solid mass on left sided ovary was found on laparotomy. Histopathological examination of the mass showed well differentiated sertoli cell tumor. Tumors of the stroma (Leydig cells) and/or sex cords (Sertoli cells) represent approximately 8% of ovarian tumors and develop from the connective tissue (respectively, interstitial and nurse cells) of the ovary. Because these cells participate in ovarian hormonal function, most of the sex-cord or stromal tumors are able to secrete hormones (estrogens, androgens, corticoids), which explains the hormonal dysfunctions associated with these tumors. Their prognosis are difficult to establish; some of the tumors are almost always benign (Sertoli cell tumors, Leydig cell tumors), whereas others are malignant but with more-or-less delayed local-regional or metastatic relapses.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 54-56